INTEGRATING ISLAMIC VALUES INTO THE DEVELOPMENT OF ORDERING, INVITATION, AND ASKING FOR PERMISSION UNIT - Nur, Nur Aliyah; Annisa Shofa Tsuraya; Rifqa Reskiawati (English Language, Linguistics, and Culture International Journal, 2022)
This research was conducted to develop English teaching materials for students based on the 2013 curriculum, especially on basic competencies 3.4 and 4.4 about Ordering, Invitation, and Asking for Permission, for the eighth-grade students at MTs Madani Pao-Pao. The researchers used R&D with the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The types of data collection in this research were quantitative and qualitative. The researchers used questionnaires for students as instrument and used validation sheet for experts. The results indicated that the students’ needs for English material of Ordering, Invitation and Asking for Permission unit are different, starting from the material organization, the content of the material and the characteristics of students. The English material used in madrasah is still general and it is not integrated with Islamic values. Therefore, "Let`s Break the Fast together" was chosen as the topic for the unit of Ordering, Invitation, and Asking for Permission based on the questionnaire. The product of English language material has been made and validated by the experts using a validation checklist, and the results of the validation checklist show that the material can be used as another references in learning Ordering, Invitation and Asking for Permission in junior high schools, especially in Islamic junior high schools. Therefore, the researchers recommend that the developed material can be used by eighth grade students in MTs Madani Pao-pao to improve their knowledge about Islamic phrases, and other researchers implement the product to evaluate its practicality and efficiency.